Pengaruh Pengendalian Internal, Budaya Organisasi, dan Moralitas pada Kecenderungan Kecurangan (Fraud) di LPD se-Kabupaten Gianyar - Eka Putra, I Putu Aditya Prastika; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 25 No 3 (2018), 2018)
This research aimed to determine the effect of internal control, organizational culture, and morality to fraud tendency. The theory used in this research are Fraud Triangle Theory and Agency Theory. The population in this study is the head of LPDs in Gianyar regency. This research using proportionate stratified random sampling. The samples were taken are 73 head of LPDs. The data collectment is done by questionnaire method. The data analysis technique used in this research is multiple linear regression technique. The results of this research showed that internal control, cultural organization and morality have negative affect on fraud tendency in LPDs in Gianyar regency. Keywords:  Internal Control, Organizational Culture, Morality, Fraud Tendency